A rib-like microstructure imitating the sparse snow ridges of the leaves of the Qinling arrow bamboo

By imitating the ridge-shaped micro-nano structure of the Qinling Arrow Bamboo Leaf surface, the problem of difficulty in reducing snow adhesion in the existing technology is solved, and the effect of significantly reducing snow adhesion strength and improving snow-sparing performance is achieved.

CN114715832BActive Publication Date: 2025-04-01NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210180336.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-26
Publication Date
2025-04-01
Estimated Expiration
2042-02-26

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively reduce the adhesion of snow, resulting in problems such as the reduction in the photoelectric conversion efficiency of solar photovoltaic panels and the excessive load on the roof of houses under the snow cover in high-latitude areas.

Method used

A ridge-rib-like micro-nano structure imitating the surface of Qinling Arrow Bamboo leaves is adopted. This structure includes a ridge-rib-like micro-structure and a mastoid-like micro-structure. Through the staggered ridge-rib-like and rib-like structure and the covered mastoid structure, an inclined pit structure is formed, which significantly reduces the adhesion strength of snow.

Benefits of technology

This structure can significantly reduce the adhesion strength of snow, improve the snow-sparing performance of the material, and effectively prevent structural damage and efficiency reduction caused by snow cover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114715832B_ABST
    Figure CN114715832B_ABST
Patent Text Reader

Abstract

The present invention discloses a ridge-shaped micro-nanostructure on the surface of an imitation Qinling arrow bamboo leaf, which can play the role of snow sparseness and snow prevention, and belongs to the field of material preparation. The imitation Qinling arrow bamboo leaf ridge-shaped microstructure includes (a) a ridge-shaped microstructure and (b) a papillary microstructure. The ridge-shaped microstructure (a) is periodically distributed in the longitudinal direction as a whole, and each period is formed by the staggered arrangement of the longitudinal "ridge"-shaped structure and the transverse "rib"-shaped structure; the ridge-shaped structure presents a "low-high-low" trend in each period, the lowest point; and the highest point; connected by rib-shaped twill, the whole constitutes a number of rectangular small units, the four sides of the square are slightly higher, and the center is concave; the inclined micro-concave structure formed by the combination of ridge-shaped structures constitutes the first layer of microstructure of the snow sparse surface of the imitation Qinling arrow bamboo leaf, that is, the ridge-shaped microstructure (a); the papillary microstructure (b) is evenly distributed on the surface of the entire ridge-shaped microstructure (a), which is the second layer of structure. The present invention analyzes the snow sparse mechanism of the microstructure surface in detail and the example data proves that it can significantly reduce the snow adhesion strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a ridge-shaped micro-nano structure imitating the surface of a Qinling arrow bamboo leaf, which can play the role of snow repelling and snow prevention, and belongs to the field of material preparation. Background Art

[0002] Snow, as a common climate phenomenon in nature, often appears in human works of art. A moderate amount of snowfall helps to protect crops from the cold in winter, but long-term snow cover in high-latitude areas will seriously affect human production and life. For example, once solar photovoltaic panels in high-altitude areas are covered with snow for a long time, their light energy conversion efficiency will drop significantly; for common light steel structure houses, excessive snow accumulation on the roof will cause the load on the house to exceed the standard. Once snowfall is accompanied by strong winds, the uneven distribution of snow on the roof will cause local instability of the structure, which will cause a chain reaction and cause the house to collapse.

[0003] Although snow and ice have the same chemical composition, their physical and chemical properties are significantly different. Although super-hydrophobic and super-lubricating surfaces have been proven to be effective in the field of ice prevention in recent years, many studies at home and abroad have shown that super-hydrophobic and super-lubricating surfaces cannot effectively reduce the adhesion of snow, and snow and ice cannot be confused. For snow with multiple pores, multiple morphologies, and multiple densities, designing a surface that is not easy to adhere to snow and can easily fall off under the action of micro-forces even if it comes into contact with snow is currently a hot topic in the field of bionic surfaces. Summary of the invention

[0004] The inspiration for the research on super-hydrophobic surfaces comes from the self-cleaning effect of water droplets rolling off the surface of lotus leaves. Similarly, we found that in the Qinling Mountains, which is more than 2,000 meters above sea level, a plant called Qinling Arrow Bamboo grows. When the entire Qinling Mountains are covered with snow in winter, its leaf surface remains green and snow-free. Even if there is a small amount of snow on the surface, it can easily fall off with very weak vibrations.

[0005] We used an air-floating snow adhesion measurement device to measure the snow adhesion strength on the surface of the leaves of the arrow bamboo in Qinling, and compared it with the snow adhesion strength of common metals, organic glass and other materials in the existing literature. The experimental results show that the snow adhesion strength on the front of the leaves of the arrow bamboo in Qinling is roughly 10-15 Pa, while the snow adhesion strength of common metals such as aluminum, stainless steel, and copper is around 100 Pa. The snow adhesion strength of polymer composite materials such as organic glass is about 30-100 Pa. At the same time, we also tested the snow adhesion strength of common anti-icing surfaces, and the measured snow adhesion strength of super-hydrophobic surfaces was in the range of 20-30 Pa. Therefore, the above experiments prove that the surface microstructure of the front surface of the arrow bamboo leaves in Qinling has excellent snow-repelling performance and can significantly reduce the snow adhesion strength. Its surface snow-repelling performance is significantly better than that of other existing material surfaces, including the lowest snow adhesion strength on the surface of the arrow bamboo leaves in common anti-icing surfaces.

[0006] Our research group has studied the multi-layer unequal height micro-nano composite structure on the back of the Qinling Arrow Bamboo, and found that the super-hydrophobic property can be used for the bionic preparation of anti-icing surfaces. Based on the research on the excellent snow-repelling properties of the front of the Qinling Arrow Bamboo leaves, this paper proposes a ridge-shaped snow-repelling micro-nano structure.

[0007] The ridge-rib microstructures of the leaves of the Qinling Arrow Bamboo proposed in the present invention include (a) ridge-rib microstructures and (b) papillary microstructures. The front structure of the Qinling Arrow Bamboo leaves is distributed periodically along the growth direction (longitudinal direction) of the bamboo leaves. Each period is composed of a longitudinal "ridge" structure and a transverse "rib" structure arranged alternately. The ridge structure presents a "low-high-low" trend in each period, with the lowest point ( Figure 1 No. 1) and the highest point ( Figure 1 No. 2) are connected by rib-like diagonal lines, forming a number of small rectangular units as a whole. The four sides of the square are slightly higher and the center is concave. In the ridge-like microstructure, the spacing z1 between the "ridges" and the "ridge" structures is between 160-200μm; the height difference h1 between the lowest point and the highest point of the ridge-like structure is 20-30μm; the lowest point of the ridge structure is smoothly connected by a semi-cylindrical structure with a radius r1 of 20-30μm; the width z2 at the highest point is 20-30μm. In the rib-like microstructure, the spacing between the "ribs" is 40-50μm; the rib-like structure is semi-cylindrical as a whole, with an irregular cross-sectional shape, and the height difference of the connecting ridge-like structures, so it presents a cross-sectional shape with one side high and the other side low ( Figure 3 The rib width is 10-20 μm. The inclined micro-concave structure formed by the combination of ridge-like structures constitutes the first layer of microstructure on the surface of the Qinling arrow bamboo leaf. In addition, there are several papillary structures on the entire surface of the arrow bamboo ( Figure 2 ) The mastoid structure is the smallest, a hemispherical structure with a size of 5-8μm and a spacing of 10-16μm. It is evenly distributed over the entire surface and is distributed above the previous layer of structure. It is the second layer of structure.

[0008] In the present invention, the above two structural layers can be prepared by metal, inorganic non-metallic materials, and polymer materials. Metal materials such as aluminum, copper, steel, etc., and their alloy materials, inorganic non-metallic materials such as PDMS (polydimethylsiloxane), photoresist, etc.

[0009] The present invention proposes a snow-removing microstructure surface imitating the Qinling Arrow Bamboo Leaf, which can significantly reduce the snow adhesion strength. The snow-removing mechanism of the microstructure surface is:

[0010] Preliminary studies have shown that the snow adhesion strength is significantly affected by the change of surface roughness. Sojoudi et al. studied the change of snow adhesion strength on aluminum surfaces with different roughness. The experimental results showed that with the increase of surface roughness, the snow adhesion strength first increased and then decreased. The snow adhesion strength decreased significantly after the roughness RMS value was greater than 200. We used laser confocal microscopy to measure the surface roughness of the sparse snow microstructure of Qinling arrow bamboo leaves. The RMS value range was [250,350], indicating that the surface roughness of this structure can effectively reduce the snow adhesion strength. Since the inclined pit structure is comparable to the snow particle size, a small amount of snow particles will stay in the pit structure when contacting the surface, which transforms the interfacial adhesion between snow and the surface into a combination of snow-snow adhesion and snow-surface adhesion. A layer of snow particles attached to the surface acts as a lubricating layer, thereby effectively reducing the snow adhesion strength.

[0011] In addition, for porous, multi-morphological, and multi-density media such as snow, the academic community usually divides snow into dry snow and wet snow based on its water content (LWC). At present, -1°C is generally used as the approximate temperature for distinguishing dry and wet snow. Snow below this temperature is considered dry snow, and snow above this temperature is considered wet snow. The snow shedding mechanism of dry snow has been mentioned before. For wet snow, the LWC content in the snow sample is relatively high, and the free water in the snow will form a water film between the snow and the surface due to the effect of gravity. The inclined pit structure of the snow shedding microstructure imitating the Qinling Arrow Bamboo Leaf is conducive to the spreading of the water film. The water film is fixed on the surface of the structure, so that the solid-solid interface is transformed into a solid-liquid interface, effectively reducing the adhesion of wet snow.

[0012] Adhesion work is the change in free energy when the unit area of ​​two media A and B is moved from contact to separation to infinite distance. Adhesion force is essentially caused by intermolecular interaction, which is manifested as the combined force of van der Waals force, electrostatic force, covalent bond and other forces. These forces, such as van der Waals force, are very sensitive to the interatomic distance, so the roughness of the solid surface makes the actual contact only occur on the rough peaks of a very small part of the contact area. The surface of the microstructure of the Qinling arrow bamboo leaf sparse snow is covered with hemispherical papillae structures, so the interaction force between snow particles and the surface only occurs on the surface of the papillae structure, and the actual contact area is greatly reduced, thereby further reducing the adhesion force. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is an axonometric drawing imitating the sparse snow ridge rib-like microstructure of the Qinling Arrow Bamboo leaves.

[0014] Figure 2 This is a top view of the sparse snow ridge rib-like microstructure of the Qinling Arrow Bamboo leaves.

[0015] Figure 3 This is a cross-sectional diagram of the rib-like structure of the leaves of Qinling Arrow Bamboo, and the shaded part is the rib structure.

[0016] Figure 4 This is a cross-sectional dimension diagram imitating the sparse snow ridge rib structure of Qinling Arrow Bamboo leaves. Specific implementation methods

[0017] The following examples further describe and demonstrate the preferred embodiments within the scope of the present invention. These examples are given for illustrative purposes only and are not to be construed as limiting the present invention.

[0018] Specific implementation case 1:

[0019] The ridge-rib microstructure imitating the Qinling arrow bamboo leaf is prepared by secondary reshaping of the arrow bamboo leaf. PDMS is used to cover the surface of the arrow bamboo leaf, and after curing, it is demolded to form a negative template. The PDMS negative template is reshaped by epoxy resin to obtain a ridge-rib microstructure. The spacing between the first layer of ridge structures is 200 microns, the width of the ridge structure and the rib structure are both 30 microns, and the height difference of the ridge structure is 20 microns. The highest ridge structure and the lowest structure are smoothly transitioned by an inclined surface, and a square pit is formed by combining the rib structure. The papillary structure covers the first layer of structure, with an average diameter of 3 microns. Specific implementation method 2

[0021] The substrate and microstructure surface are made of aluminum and processed by femtosecond laser. The first layer is a high and low staggered inclined structure composed of a ridge-rib periodic structure. The ridge structure spacing is 180 microns, the ridge structure width is 30 microns, the rib structure width is 20 microns, the ridge structure height difference is 30 microns, the lowest point and the highest point are connected by an inclined plane, and the inclined pit structure is formed by combining the rib structure. The second layer of mastoid structure is simplified to a hemispherical structure with a diameter of 5 microns, covering the first layer of structure. The upper surface of the substrate material layer is a smooth surface.

[0022] Snow removal performance test

[0023] The epoxy resin material with the ridge-like microstructure of the leaves of the imitation Qinling arrow bamboo prepared in Example 1 was subjected to a comparative test of snow adhesion strength. The air-floating snow adhesion measuring device was used to measure the snow adhesion strength of the epoxy resin material with the ridge-like microstructure of the leaves of the imitation Qinling arrow bamboo and the surface of the unstructured pure epoxy resin. At the same time, common materials were measured: aluminum, copper, plexiglass, and super-hydrophobic coating to compare the snow-repelling performance of the structure of the present invention. The experimental results show that the snow adhesion strength of the epoxy resin material with the ridge-like microstructure of the leaves of the imitation Qinling arrow bamboo is about 40Pa, which is 64% lower than the snow adhesion strength of the pure epoxy resin (110Pa). The snow adhesion strengths of 6061 aluminum, copper, plexiglass, and super-hydrophobic coating are 140Pa, 120Pa, 65Pa, and 60Pa, respectively. The epoxy resin material with the ridge-like microstructure of the leaves of the imitation Qinling arrow bamboo in the tested sample has the lowest snow-repelling strength, and the structure can effectively improve the snow-repelling performance of the material.

Claims

1. A rib-like microstructure imitating the sparse snow ridges of Qinling arrow bamboo leaves, characterized in that: Includes (a) ridge-like microstructures, (b) papillary microstructures, The ridge-rib-like microstructure (a) is distributed periodically in the longitudinal direction as a whole, and each period is formed by the longitudinal "ridge"-like structure and the transverse "rib"-like structure arranged alternately; the ridge-like structure presents a "low-high-low" trend in each period, and the lowest point and the highest point are connected by rib-like diagonal lines, forming a plurality of rectangular small units as a whole, with the four sides of the rectangle slightly higher and the center concave; the inclined micro-concave structure formed by the combination of the ridge-rib-like structures constitutes the first layer of microstructure of the surface of the Qinling arrow bamboo leaf sparse snow, namely the ridge-rib-like microstructure (a); The papillary microstructure (b) is evenly distributed on the surface of the entire ridge-like microstructure (a) and is a second-layer structure; In the ridge-rib microstructure, the spacing z1 between the "ridge" and the "ridge" structure is between 160-200μm; the height difference h1 between the lowest point and the highest point of the ridge structure is 20-30μm; the lowest point of the ridge structure is smoothly connected by a semi-cylindrical structure, and the radius r1 is 20-30μm; the width z2 of the highest point is 20-30μm; in the rib microstructure, the spacing between the "ribs" is 40-50μm; the rib structure is semi-cylindrical as a whole, with an irregular cross-sectional shape, and the height difference connecting the ridge structures, so it presents a cross-sectional shape with one side high and the other side low; the rib width is 10-20μm.

2. A ridge-like microstructure imitating the Qinling arrow bamboo leaf sparse snow as claimed in claim 1, characterized in that: The papillary microstructure is a hemispherical structure with a size of 5-8 μm and a spacing of 10-16 μm.

3. A ridge-like microstructure imitating the sparse snow ridges of the leaves of the Qinling arrow bamboo as claimed in any one of claims 1-2, characterized in that: The materials of the ridge-shaped microstructure (a) and the papillary microstructure (b) are metal, inorganic non-metallic material or polymer material.

4. A ridge-like microstructure imitating the Qinling Feather Bamboo leaf sparse snow as claimed in claim 3, characterized in that: The ridge-shaped microstructure (a) and the papillary microstructure (b) are made of aluminum, copper, steel or alloy materials.

5. A ridge-like microstructure imitating the Qinling Feather Bamboo leaf sparse snow as claimed in claim 3, characterized in that: The materials of the ridge-shaped microstructure (a) and the papillary microstructure (b) are PDMS or photoresist.

Citation Information

Patent Citations

  • Constructional panel

    AU2002244501B2

  • Ice coating prevention surface of bionic micro-nano composite structure and preparation method thereof

    CN102492945A